Challenges in Implementing the TaRL Approach in Mathematics Learning for Grade VI Students - Urfah, Mawaddatul; Nurjayanti, Anisa; Ningsih, Setia Ayu; Nugraha, Enung; Juhji, Juhji (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The purpose of this research is to discover the problems that occur in the field by describing the problems or challenges teachers face in learning by applying the TaRL approach to mathematics subjects in class VI A SDN Banjar Agung 4. This research is a qualitative descriptive research. The primary and secondary data explored in this study are primary and secondary. Research data were obtained through interviews, observations, and documentation. Data analysis was done through data reduction, presentation, and conclusion drawing. Data validity was tested through triangulation techniques. The results showed that several problems challenge teachers in implementing the TaRL approach, namely (1) limited teacher understanding of TaRL concepts and techniques, (2) heterogeneous classroom environment with a large number of students, namely 36 students, (3) limited time and costs and monitoring the implementation of the learning process, (4) lack of resource support such as the preparation of learning tools, and (5) limited training and socialization regarding process planning and learning evaluation using the TaRL approach. The solution that can be given is that the school or principal, as the leader in the basic education unit, needs to provide resource support in the form of providing training on the TaRL learning approach to teachers and financial support in the form of comfortable facilities, learning resources, and financial support.